Prognostic significance of preoperative PNI and CA19-9 for pancreatic ductal adenocarcinoma: A multi-institutional retrospective study - Itoh, Shinji; Tsujita, Eiji; Fukuzawa, Kengo; Sugimachi, Keishi; Iguchi, Tomohiri; Ninomiya, Mizuki; Maeda, Takashi; Kajiyama, Kiyashi; Adachi, Eisuke; Uchiyama, Hideaki; Utsunomiya, Tohru; Ikeda, Yasuharu; et al. (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2021)
The aim of this study was to investigate the clinical value of nutritional and immunological prognostic scores as predictors of outcomes and to identify the most promising scoring system for patients with pancreatic ductal adenocarcinoma (PDAC) in a multi-institutional study. Data were retrospectively collected for 589 patients who underwent surgical resection for PDAC. Prognostic analyses were performed for overall (OS) and recurrence-free survival (RFS) using tumor and patient-related factors, namely neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, Prognostic Nutritional Index (PNI), Glasgow Prognostic Score (GPS), modified GPS, C-reactive protein-to-albumin ratio, Controlling Nutritional Status score, and the Geriatric Nutritional Risk Index. Compared with PDAC patients with high PNI values (≥46), low PNI (<46) patients showed significantly worse overall survival (OS) (multivariate hazard ratio (HR), 1.432; 95% CI, 1.069–1.918; p = 0.0161) and RFS (multivariate HR, 1.339; 95% CI, 1.032–1.736; p = 0.0277). High carbohydrate antigen 19–9 (CA19-9) values (≥450) were significantly correlated with shorter OS (multivariate HR, 1.520; 95% CI, 1.261–2.080; p = 0.0002) and RFS (multivariate HR, 1.533; 95% CI, 1.199–1.961; p = 0.0007). Stratification according to PNI and CA19-9 was also significantly associated with OS and RFS (log rank, P < 0.0001). Our large cohort study showed that PNI and CA19-9 were associated with poor clinical outcomes in PDAC patients following surgical resection. Additionally, combining PNI with CA19-9 enabled further classification of patients according to their clinical outcomes.